A cross-sectional evaluation of opioid dispensing competencies in final-year Pharm-D students: a multicenter study from Punjab, Pakistan - Mubarak, Naeem; Rana, Fatima Rahman; Zahid, Taheer; Ijaz, Umm-E-Barirah; Shabbir, Afshan; Bari, Ahtesham Ghulam; Niaz, Bisma; Kanwal, Sabba; Ur Rahman, Nasira Saif; Iqbal, Zahid; Khan, Asad Majeed; Zin, Che Suraya; et al. (Dove Medical Press, 2024)
Background: The opioid crisis continues to be a public health concern worldwide due to the high rates of misuse and associated mortality. Opioid dispensing competencies are critical for pharmacy graduates to promote the rational use of opioids. Purpose: To evaluate the opioids dispensing competencies among the final year Pharm-D students in Punjab, Pakistan. Design: A multicenter cross-sectional study. Methods: A validated survey was used to evaluate 11 competencies related to opioid use from the final year Pharm-D students from diversely located accredited institutes. On a summative scale, correct response to each survey item was worth a score/point.Descriptive statistics was used for categorical variables while independent t-test computed group differences. Results: A total of n = 661 final year Pharm-D students from 28 institutes (8 public and 20 private) completed the survey with an overall response rate of 78.5%. Comparatively, the students who had either completed a community or hospital internship, or studying in the educational institutions located in the provincial capital demonstrated a significant higher competency score. There was no significant difference in the overall mean competency scores based on gender or system of assessment used in the Pharm-D degree programs. Among eleven opioid competencies, students received the lowest scores for “opioid overdose management”, “opioid monitoring” and “therapeutic uses of opioids”. Conclusion: Pharm-D students in Pakistan require additional training and skills on many of the opioids related competencies to ensure patient’s safety in healthcare settings. There is a need to revise the curriculum and teaching methodologies to improve the competencies of Pharm-D students in opioid dispensing.